2018
DOI: 10.3892/or.2018.6784
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone�H induces the apoptosis of human oral squamous cell carcinoma cells via regulation of matrin�3

Abstract: Licochalcone H (LCH) is a chemical compound that is a positional isomer of licochalcone C (LCC), a chalconoid isolated from the root of Glycyrrhiza inflata, which has various pharmacological properties including anti-inflammatory, antioxidant, antitumor, and anticancer effects. However, the efficacy of LCH on cancer cells has not been investigated. The present study examined the effects of LCH on cell proliferation, induction of apoptosis, and the regulation of matrin 3 (Matr3) protein in oral squamous cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…This may also suggest that forced overexpression of MATR3 in the MATR3-low BLBC cells such as MDA-MB-231 may cause apoptotic cell death, which possibly makes generating stable MATR3-overexpressing cell lines unsuccessful. In the oral squamous cell carcinoma and normal endothelial cells, however, silencing MATR3 using siRNA promoted cell death [35,36], which indicates that the pro-apoptotic function of MATR3 may be cell-context dependent.…”
Section: Discussionmentioning
confidence: 99%
“…This may also suggest that forced overexpression of MATR3 in the MATR3-low BLBC cells such as MDA-MB-231 may cause apoptotic cell death, which possibly makes generating stable MATR3-overexpressing cell lines unsuccessful. In the oral squamous cell carcinoma and normal endothelial cells, however, silencing MATR3 using siRNA promoted cell death [35,36], which indicates that the pro-apoptotic function of MATR3 may be cell-context dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Just a few studies were conducted; for example, Yang et al performed Western blot and RNA immunoprecipitation assay to find that the lncRNA SNHG1 was directly interacted with MATR3 to promote neuroblastoma progression [52]. Nho et al observed the "Licochalcone H" could suppress cell viability and induce apoptosis in human oral squamous cell lines by suppression of MATR3 [53]. In short, previous articles indicated that the hub genes involved in the two modules showed a variety of physiological and pathological functions in breast cancer as an integrated interaction network including lncRNAs and TFs, which have significant prognosis capability and could be used as prognostic signatures of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Diosmin and hesperidin were not more when used in combination than when either was delivered alone, indicating that they do not act synergistically (Tanaka et al, 1997). (Li, Huang et al, 2013); 5 ; 6 (Li et al, 2010); 7 ; 8 (Ye et al, 2004); 9 (Lin et al, 2007); 10 ; 11 ; 12 (Lee et al, 2015); 13 ; 14 (Ji et al, 2018); 15 (Shih et al, 2017); 16 (Chou et al, 2018); 17 (Lai et al, 2013); 18 (Zhao et al, 2019); 19 ; 20 (Chen et al, 2012); 21 (Maggioni et al, 2014); 22 (Li et al, 2018); 23 (Gao et al, 2015); 24 (Tao et al, 2015); 25 (Tao et al, 2014); 26 (Babich et al, 2007); 27 (Pons-Fuster López et al, 2017); 28 (Mohan et al, 2007); 29 (Czyżewska et al, 2016); 30 (Yao et al,2005); 31 (Hua et al, 2006); 32 (Yang et al, 2017); 33 (Prasad & Katiyar, 2012); 34 ; 35 ; 36 (Hsia et al, 2016); 37 ; 38 (Nho et al, 2019); 39 (Cho et al, 2014); 40 ; 41 ; 42 (Chen et al, 2006); 43 (Won et al, 2018); 44 (Baba et al, 2015); 45 (Liu et al, 2016).…”
Section: Flavonesmentioning
confidence: 99%
“…A simplified schematic effect of flavonoids on tongue cancer cells. The numbers in each reference correspond to the numbers in figure: 1 (Celińska‐Janowicz et al, ); 2 (Masuelli et al, ); 3 (Maggioni et al, ); 4 (Li, Huang et al, ); 5 (Li et al, ); 6 (Li et al, ); 7 (Yang et al, ); 8 (Ye et al, ); 9 (Lin et al, ); 10 (Kim et al, ); 11 (Yang et al, ); 12 (Lee et al, ); 13 (Lin, Chen et al, ); 14 (Ji et al, ); 15 (Shih et al, ); 16 (Chou et al, ); 17 (Lai et al, ); 18 (Zhao et al, ); 19 (Huang et al, ); 20 (Chen et al, ); 21 (Maggioni et al, ); 22 (Li et al, ); 23 (Gao et al, ); 24 (Tao et al, ); 25 (Tao et al, ); 26 (Babich et al, ); 27 (Pons‐Fuster López et al, ); 28 (Mohan et al, ); 29 (Czyżewska et al, ); 30 (Yao et al,); 31 (Hua et al, ); 32 (Yang et al, ); 33 (Prasad & Katiyar, ); 34 (Chen et al, ); 35 (Hou et al, ); 36 (Hsia et al, ); 37 (Oh et al, ); 38 (Nho et al, ); 39 (Cho et al, ); 40 (Shen et al, ); 41 (Zeng et al, ); 42 (Chen et al, ); 43 (Won et al, ); 44 (Baba et al, ); 45 (Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%